Phytochemical study and evaluation of the antidiabetic and antihyperglycemic activities of the fruit extracts of Physalis peruviana L. (Solanaceae) - Damien S.T. Tshibangu; Fortune S. Kavugho; Carlos N. Kabengele; Adrien T. Masunda; Gédéon N. Bongo; Giresse N. Kasiama; Domaine T. Mwanangombo; Clément L. Inkoto; Clément M. Mbadiko; Benjamin Z. Gbolo; Désiré M. Musuyu; Dorothée D. Tshilanda; et al. (Phytomedicine Plus)
The aim of the study was to evaluate the antidiabetic and antihyperglycemic activities of Physalis peruviana L. (PP) fruit extracts as well as to determine the structure-activity relationship of some molecules from this plant using molecular docking. Medically, the plant has been used traditionally to treat diabetes and other diseases.The methanolic extract showed the highest yield of 12.01 %, while the lower yield of 2.74 % was observed in the ethyl acetate one. On the one hand, polyphenols (flavonoids, tannins and anthocyanins) were identified in the aqeous extract, while free quinones were not ; on the other hand, steroids and terpenoids were revealed in the organic extract, while bound quinones were absent. The quantitative analysis showed high level of some secondary metabolites (polyphenols, flavonoids, hydrolyzable and tannins), but low level of anthocyanins. Mineralogical analysis showed that the species contains minerals, essential for the organism and for the survival of the plant at significant concentrations (K, P, Ca, Mg, Na, Zn, etc.). The methanolic extracts of the species indicated high antidiabetic activity, comparatively to other extracts. The results of the antihyperglycemic test showed that the methanolic extract significantly inhibited orally induced hyperglycemia in mice. This inhibition was confirmed by molecular docking analyzes by interacting the molecules of the studied plant with two receptors, alpha-glucosidase (PDB id: 3WY1) and the kinase domain of the 5HHW insulin receptor.These experimental results lend credibility to the use of this species in traditional Congolese medicine to treat type 2 diabetes.